One-step synthesis of site-specific antibody-drug conjugates by reprograming IgG glycoengineering with LacNAc-based substrates - Wei Shi; Wanzhen Li; Jianxin Zhang; Tiehai Li; Yakai Song; Yue Zeng; Qian Dong; Zeng Lin; Likun Gong; Shuquan Fan; Feng Tang; Wei Huang (Elsevier, 2022)
Glycosite-specific antibody‒drug conjugatess (gsADCs), harnessing Asn297 N-glycan of IgG Fc as the conjugation site for drug payloads, usually require multi-step glycoengineering with two or more enzymes, which limits the substrate diversification and complicates the preparation process. Herein, we report a series of novel disaccharide-based substrates, which reprogram the IgG glycoengineering to one-step synthesis of gsADCs, catalyzed by an endo-N-acetylglucosaminidase (ENGase) of Endo-S2. IgG glycoengineering via ENGases usually has two steps: deglycosylation by wild-type (WT) ENGases and transglycosylation by mutated ENGases. But in the current method, we have found that disaccharide LacNAc oxazoline can be efficiently assembled onto IgG by WT Endo-S2 without hydrolysis of the product, which enables the one-step glycoengineering directly from native antibodies. Further studies on substrate specificity revealed that this approach has excellent tolerance on various modification of 6-Gal motif of LacNAc. Within 1 h, one-step synthesis of gsADC was achieved using the LacNAc-toxin substrates including structures free of bioorthogonal groups. These gsADCs demonstrated good homogeneity, buffer stability, in vitro and in vivo anti-tumor activity. This work presents a novel strategy using LacNAc-based substrates to reprogram the multi-step IgG glycoengineering to a one-step manner for highly efficient synthesis of gsADCs.